1990
DOI: 10.1172/jci114454
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridization evidence for angiotensinogen messenger RNA in the rat proximal tubule. An hypothesis for the intrarenal renin angiotensin system.

Abstract: We examined angiotensinogen gene expression in rat kidney by in situ hybridization histochemistry. Using a rat cRNA probe to angiotensinogen, we demonstrated angiotensinogen mRNA to be localized predominantly in the proximal renal tubule, with considerably lesser amounts in distal tubular segments and glomerular tufts. Previous studies have localized renin immunoreactivity to the juxtaglomerular cells, glomerular tufts, and proximal tubules. Such findings provide further evidence for a local tissue renin angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
208
2
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(219 citation statements)
references
References 24 publications
7
208
2
2
Order By: Relevance
“…The results described by Ohashi et al, in addition to previous studies from Kobori's group that found elevated urinary AGT levels in patients with chronic kidney disease including patients with diabetes, confirm that urinary AGT levels can function as an Proximal tubule ACE, AGT, AII, Ang 1-7, renin, renin pro-receptor, AT1 6,7 Distal tubule AGT, AII 8 Collecting duct ACE, AGT, AII, Ang 1-7, renin, renin pro-receptor, AT1 8,9 Abbreviations: ACE, angiotensin I-converting enzyme; AGT, angiotensinogen; Ang II receptors; AT-1 and AT-2 subtypes; RAS, rennin-angiotensin system.…”
Section: Are There Clinical Implications For Increased Intrarenal Agt?supporting
confidence: 68%
See 1 more Smart Citation
“…The results described by Ohashi et al, in addition to previous studies from Kobori's group that found elevated urinary AGT levels in patients with chronic kidney disease including patients with diabetes, confirm that urinary AGT levels can function as an Proximal tubule ACE, AGT, AII, Ang 1-7, renin, renin pro-receptor, AT1 6,7 Distal tubule AGT, AII 8 Collecting duct ACE, AGT, AII, Ang 1-7, renin, renin pro-receptor, AT1 8,9 Abbreviations: ACE, angiotensin I-converting enzyme; AGT, angiotensinogen; Ang II receptors; AT-1 and AT-2 subtypes; RAS, rennin-angiotensin system.…”
Section: Are There Clinical Implications For Increased Intrarenal Agt?supporting
confidence: 68%
“…1,2 In addition to the well-characterized systemic RAS, the presence of a local intrarenal RAS has now been generally accepted. The mRNA and functional proteins of the RAS, including angiotensinogen (AGT), renin, prorenin receptor, 3 angiotensin I-converting enzyme and Ang II receptors (AT-1 and AT-2 subtypes), are expressed in rat mesangial cells, 4,5 mouse and rat immortalized renal proximal tubular cells 6,7 and rat collecting duct cells 8,9 (Table 1).…”
mentioning
confidence: 99%
“…47,48,50,52 Proximal tubular cells express mRNA [54][55][56] and protein 53,57 for ACE and Aogen. [58][59][60][61] In vivo evidence that proximal tubular cells may synthesize Ang II has also been reported. 62 The above studies indicate the presence of a functional renal tubular RAAS, which likely has an important function in regulating sodium and fluid balance, and hence BP.…”
Section: Intrarenal Raasmentioning
confidence: 88%
“…The proximal tubular epithelium expresses AGTN in the normal kidney and in some diseased kidneys. 7,31 However, in the fibrosing kidney, the interstitial FbLCs may produce AGTN rather than the proximal tubular epithelial cells because of significant degeneration of the latter. These dynamic changes in REN and AGTN suggest that the enzymesubstrate reaction occurs in the fibrosing kidney.…”
Section: Discussionmentioning
confidence: 99%